HUKUM PELAKSANAAN IBADAH HAJI MENGGUNAKAN UANG HARAM MENURUT FIQIH KONTEMPORER - Nurul Siti Khadijah; Widya Indah Pratiwi; An'nisa Aulia Nur Azni; Sarah Lisfiza; Nabila Salsabilla (Yayasan Dar Arrisyah Indonesia, 2025)
This paper explores the protection of women's rights within marriage from the perspective of Islamic law, particularly as codified in Indonesia's legal framework. Using a normative juridical approach, this study examines primary and secondary legal sources—including the Qur’an, Hadith, the Compilation of Islamic Law (KHI), and relevant Indonesian statutes—to assess the extent and implementation of women’s legal protections in marital life. Key areas of focus include women’s rights to maintenance, equitable treatment, protection against domestic violence, and fair division of property post-divorce. The analysis reveals that Islamic legal doctrines, when interpreted within the framework of maqāṣid al-sharī‘ah (objectives of Islamic law) and siyasah syar‘iyyah (Islamic governance), provide a robust foundation for gender justice and legal empowerment of women. However, cultural patriarchal biases and institutional shortcomings continue to hinder effective enforcement. The study underscores the role of the state in safeguarding women’s rights as part of its obligation to uphold public welfare and eliminate gender-based discrimination. Ultimately, the paper advocates for a gender-responsive reinterpretation of Islamic norms and stronger legal institutions to ensure substantive equality and protection for women in marriage.